Evaluation of tourists satisfaction towards firefly industry in Sabah using importance-performance analysis model - Syazlina Saib; Mahadimenakbar Mohamed Dawood; Fiffy Hanisdah Saikim (e-VIBS, Faculty of Science and Natural Resources, 2016)
This paper focuses on the human dimensions of the firefly watching experience in Sabah with the using of Importance-performance analysis (IPA). The objectives are to investigate the motivations of tourists participating in firefly tours and to assess tourist’s satisfaction with the environmental and tour services offered in Sabah using IPA analysis. The methods included site-based distribution of questionnaire to firefly tour participants at several firefly-watching sites in Sabah. Next, the importanceperformance analysis was performed using the importance and satisfaction mean scores. The IPA analysis identified 10 environmental and tour features of management concern. Overall, respondents were very satisfied with the tourism industry in Sabah stating that they would recommend the tour (88.6%) to others. Most participants were very satisfied with the interest in firefly (78.8%), proximity to fireflies (55.92%) and the number of fireflies seen (54.29%). As conclusion, this study provides a greater understanding of tourist’s motivation and satisfaction towards the firefly-watching industry in Sabah with the assist of Importance-performance analysis model.